Colorimetric determination of phosphoric acid leakage for phosphoric acid-doped polybenzimidazole membrane fuel cell applications - Jeong, Yeon Hun; Jung, Ju Hae; Choi, Euiji; Han, Seungyoon; Begley, Alina Irene; Yoo, Sung Jong; Jang, Jong Hyun; Kim, Hyoung-Jtihn; Nam, Suk Woo; Lee, Kwan-Young; Kim, Jin Young (ELSEVIER, 2015)
A simple and precise colorimetric method for analyzing phosphoric acid leakage in phosphoric acid-doped polybenzimidazole membrane fuel cells is described. The developed method is based on the colorimetric determination from a rapid formation of molybdenum blue color by the reduction reaction of molybdate ions in the presence of phosphoric acid in the acidic medium. The color is stable up to a few months and can be used for the sensitive and accurate detection of phosphoric acid electrolyte which is discharged from the fuel cell during operation. Tests with a wide concentration range of phosphate compounds showed that it permits determination of phosphoric acid up to nanogram quantities. The developed detection method assists monitoring the phosphoric acid contents and developing stable operation strategies of fuel cells. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: HIGH-TEMPERATURE PEMFC; ELECTROLYTE MEMBRANES; PERFORMANCE